Pesquisa e produção de conhecimento sobre a América Latina na ciência política brasileira - Damasceno, João Pedro Tavares (2014)
The Brazilian Political Science has been studying a range of topics regarding Brazil itself or its states. Researches of Latin American approach still seem to be incipient. This work aims to discuss about the studies with reference to Latin America in Brazilian Political Science, i.e., the scientific production of who works with this subject regarding several topics involving Latin America, one or more countries of this zone, unless Brazil is not the only point of research. This exception means that a Brazilian case study realized by a professional of national Political Science cannot be part of what is produced in Brazil about Latin America, unless another point of observation is added to it. The database comes from CAPES, CNPq and some journals. Considering it, it is possible to understand that there was progress in scientific production about Latin America in the Brazilian Political Science, however this still is not enough for a country that aims to deepen its inclusion in the zone. One possible explanation is the methodological problems that national Political Science faces towards the use of tools that allows comprising a bigger number of case studies including other Latin Americans countries, besides Brazil.